House of whispers. Volume three, Watching the watchers - Hopkinson, Nalo (Hopkinson, Nalo, House of Whispers, 2020)
"What is it like to have the House of Whispers as the house next door? Follow a young woman as she finds out. This unexpected domestic mishap leaves her in dire need of aid from Erzulie and Ogun... whether she knows it or not."--